2017
DOI: 10.1016/j.neuron.2017.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Gating of Parvalbumin Interneuron Function by the Perineuronal Net Protein Brevican

Abstract: Activity-dependent neuronal plasticity is a fundamental mechanism through which the nervous system adapts to sensory experience. Several lines of evidence suggest that parvalbumin (PV+) interneurons are essential in this process, but the molecular mechanisms underlying the influence of experience on interneuron plasticity remain poorly understood. Perineuronal nets (PNNs) enwrapping PV+ cells are long-standing candidates for playing such a role, yet their precise contribution has remained elusive. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
306
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(339 citation statements)
references
References 53 publications
27
306
4
2
Order By: Relevance
“…In this study, we observe that the frequency of SWR events is increased in hippocampal slices that are pretreated with proteases known to disrupt integrity of the PNN (Bikbaev et al, ). This suggests that PNN disruption is sufficient not only to reduce glutamatergic input to individual PV cells as previously described (Favuzzi et al, ), but to affect the dynamics of large‐scale population events initiated by hippocampal PCs. Since PV FSIs represent the predominant cell type known to be ensheathed by a PNN (Pantazopoulos and Berretta, ), PNN digestion likely affects PC excitability through modulation of inhibitory input from the PV population.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, we observe that the frequency of SWR events is increased in hippocampal slices that are pretreated with proteases known to disrupt integrity of the PNN (Bikbaev et al, ). This suggests that PNN disruption is sufficient not only to reduce glutamatergic input to individual PV cells as previously described (Favuzzi et al, ), but to affect the dynamics of large‐scale population events initiated by hippocampal PCs. Since PV FSIs represent the predominant cell type known to be ensheathed by a PNN (Pantazopoulos and Berretta, ), PNN digestion likely affects PC excitability through modulation of inhibitory input from the PV population.…”
Section: Discussionsupporting
confidence: 70%
“…Glutamate receptors on PV interneurons are localized to soma and proximal dendrites, both of which are typically ensheathed by PNN (Favuzzi et al, ). Of interest, the subpopulation of PV cells that is rich in PNN, as determined by staining with the CSPG brevican, receives relatively robust glutamatergic input (Favuzzi et al, ). With PNN disruption released glutamate may more easily diffuse.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, genetic deletion of the PNN component brevican has been associated with altered intrinsic properties and reduced synaptic input to PV interneurons through changes in potassium channel localization and levels of GluAs (Favuzzi et al . ). Of interest, antidepressants including venlafaxine have been linked to an increased risk of seizures and disinhibition could contribute to the same.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, TnR ablation impairs spatial and motor learning 58 . Similarly, loss of brevican disrupts long-term potentiation 59 , and results in memory deficits 60 . Together, the downregulation in the expression of several synaptic ECM proteins shortly after social defeat may result in ECM composition-dependent aberrant synaptic transmission that could contribute to the observed memory deficits.…”
Section: Figure 5 Schematic Of the Main Conclusion: Ecm Imbalance Comentioning
confidence: 99%
“…Although the precise mechanisms by which PNNs regulate the activity of PV +interneurons remains elusive, PNNs have been shown to modulate the excitability and highfrequency firing of PV + -interneurons 61,62 . Recently, it was shown that mainly Brevican that is expressed by PV + -interneurons controls PV-excitability via the modulation of excitatory inputs these neurons receive, and controls molecular components of synaptic and intrinsic plasticity 60 . Conversely, hippocampus-dependent learning, and intrinsic plasticity affect activity of PV +interneurons and Brevican levels 63,60 .…”
Section: Figure 5 Schematic Of the Main Conclusion: Ecm Imbalance Comentioning
confidence: 99%